Smartphone-derived heart-rate variability and training load in a women`s soccer team - Flatt, A. A.; Esco, M. R. (International Journal of Sports Physiology and Performance, 2015)
Purpose: This study evaluated the 7-d mean and coefficient of variation (CV) of supine and standing ultrashort log-transformed root mean square of successive R-R intervals multiplied by 20 (lnRMSSDx20) obtained with a smartphone application (app) in response to varying weekly training load (TL). In addition, the authors aimed to determine if these values could be accurately assessed in as few as 5 or 3 d/wk. Methods: Nine women from a college soccer team performed daily heart-rate-variability measures with an app in supine and standing positions over 3 wk of moderate, high, and low TL. The mean and CV over 7, 5, and 3 d were compared within and between weeks. Results: The 5- and 3-d measures within each week provided very good to nearly perfect intraclass correlations (ICCs .74-.99) with typical errors ranging from 0.64 to 5.65 when compared with the 7-d criteria. The 7, 5, and 3-d supine CV and the 7-day standing CV were moderately lower during the low-load than the high-load week (P .003-.045, effect sizes 0.86-0.92), with no significant changes occurring in the other measures. Conclusion: This study supports the use of the mean and CV of lnRMSSD measured across at least 5 d for reflecting weekly values. The supine lnRMSSDx20 CV as measured across 7, 5, and 3 d was the most sensitive marker to the changes in TL in the 3-wk period.